Saving the Earth From the Dinner Table: Efforts to Reduce Food Waste Production in the Perspective of Sufism Ethics - Ibrahim, Ibrahim; Maharani, Yusmita; Ibrahim, Timothy Pascaliez; Hidayatullah, Ahmad Fauzan (UAS PRESS, 2024)
Reducing food waste is a very serious problem in the world, with a predicted increase in food demand by 50-70% by 2050. Indonesia, as a Muslim-majority country, ranks No. 2 after Saudi Arabia as the largest producer of food waste. The impact of this food waste extends to areas such as the economy, society, and the environment. The Sufism approach emphasizes simplicity, gratitude, and recognition of responsibility to nature. This approach provides a holistic solution that focuses not only on technical aspects, but also spiritual and ethical aspects. This research shows that consumption ethics in Islam influence people's behavior in managing food resources and reducing food wastage. Sufism, as a branch of mysticism in Islam, teaches the values of ethics, obedience, and wisdom in daily behavior, including reducing food waste production. By understanding food waste management behavior, this research hopes to help maximize household food management efficiency and reduce food waste.